Luminous measurement of LED lights in cost effective way using cylindrical method. (February 2017) - Haque, Fahimul; Azad, A.
Highlights: New procedure of luminous measurement using 2 different sized cylindrical black boxes. Formed equations through graphical analysis to determine luminous flux. Result shows deviation within ±4% of the rated value for different lamps. Reduced the cost to a ratio of 1:40 of the original expenditure for the arrangement. Highly efficient system for practical use, especially in developing countries. Abstract: Because of several Solar Home System (SHS) components' manufacturers in the market, overall quality of LED lamps fluctuates from organization to organization. There is an increment in unsteady quality with the number of SHS installation, which eventually causes system ineffectiveness. As a result, testing of LED lamps used in SHS plays significant role in maintaining the quality. However, existing procedures i.e. integrated sphere, goniophotometer method for lumen testing are quite costly in Bangladesh's perspective; so we have used our handmade cylindrical black box of different dimensions and sizes in CARC (previously known as CARG) lab, BRAC University. In this research we have included the testing results collected from our measurement process and also have established some relevant equations from what we have measured the total lumen of the light sources. Moreover, we used graphical analysis to find out the characteristics of different cylinders under different conditions.